2021
DOI: 10.3390/toxins13070434
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanism of Patulin from Apple Juice by Inactivated Lactic Acid Bacteria Isolated from Kefir Grains

Abstract: In the food industry, microbiological safety is a major concern. Mycotoxin patulin represents a potential health hazard, as it is heat-resistant and may develop at any stage during the food chain, especially in apple-based products, leading to severe effects on human health, poor quality products, and profit reductions. The target of the study was to identify and characterize an excellent adsorbent to remove patulin from apple juice efficiently and to assess its adsorption mechanism. To prevent juice fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Nonetheless, this phenomenon is strain-specific once different strains of the same species may have different bind capacities for specific mycotoxins [ 61 ]. Several LAB have been reported to be capable of binding PAT [ 15 , 62 ], OTA [ 63 ], and AFB1 [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this phenomenon is strain-specific once different strains of the same species may have different bind capacities for specific mycotoxins [ 61 ]. Several LAB have been reported to be capable of binding PAT [ 15 , 62 ], OTA [ 63 ], and AFB1 [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“… Petka et al (2020) supported the previous results and stated that acrylamide had an impact on the viability of L. plantarum by decreasing its count and changing its morphology which was also found in the present study by TEM for both enterococcal strains, where the outer layer became wrinkled, increasing its binding area ( Petka et al, 2020 ). It was also reported that Lactobacillus kefiranofacein was used to adsorb the mycotoxin patulin in apple juice ( Bahati et al, 2021 ). The bacteria’s cell wall was the main contributor that bound the toxin, and the thicker it was, the higher the adsorption results.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five strains tested, L. kefiranofaciens JKSP109 was the finest patulin scavenger—93% at 100 μg/L but only 56% at 200 μg/L. The adsorption capacity was found to depend on pH and the °Brix, in which the higher, the better in both cases [ 224 ].…”
Section: Lab Against Mycotoxins and Their Producersmentioning
confidence: 99%